PENGARUH KECERDASAN EMOSIONAL DAN KECERDASAN SPRITUAL TERHADAP KINERJA PERAWAT PADA RUMAH SAKIT UMUM KOTA TIDORE KEPULAUAN - Dahlan, Fadli (Jurnal Akrab Juara, 2018)
This study will explain the linkage between several variables through hypothesis testing or explanatory research. The results showed that (1) Emotional Intelligence (X1) had a positive and significant effect on nurse performance at Tidore City Public Hospital, the result of this research meant that with the Emotional Intelligence, the nurse was able to give positive contribution to the patient at Tidore City General Hospital Island. (2) and Spiritual Intelligence (X2) have a positive and significant effect on nurse's performance at Tidore Islands Public Hospital, the result of this research means that nurses do not have the ability in spiritual indicator that responsibility, confidence, justice and social awareness means that Spiritual Intelligence hence increased performance of nurse. (3) Emotional Intelligence (X1) and spiritual intelligence (X2) positive partially and simultaneously affect the Performance Nurse (Y) At Tidore Islands General Hospital.